Развој, имплементација и евалуација на напредни образовни технологии во воено образование и обука - Богатинов, Димитар (ФИНКИ, УКИМ, Скопје, 2016)
The core of this PhD dissertation is the creation of new low cost firearms simulator based on a motion-tracking sensor - Microsoft Kinect and virtual simulation VBS3. This simulator uses Microsoft Kinect SDK based application that utilizes the input from the embedded Kinect sensors to calculate the aiming point at the screen, recognizes the user's gestures and the audio inputs, and emulates commands in a simulation based on those inputs. For the evaluation process I have created three test modules that use different calibration points and mathematical frameworks to accurately transform the gunshot targeting point in proper pixel coordinate. The initial experiments with the proposed firearms simulator show that the results are accomplished by humans using the simulator and the results accomplished in the real live firearms shooting have a high correlation coefficient of 0.82. This shows that the proposed simulator can be used in firearms training, and according to the data from the survey of the test users, it is a good alternative to the existing expensive simulators available on the market. This dissertation also gives a concept how this simulator can be implemented in the education and training at the military academy and in the Macedonian army.
Докторска дисертација одбранета во 2016 година на Факултетот за информатички науки и компјутерско инженерство во Скопје, под менторство на проф. д–р Владимир Трајковиќ.
Keywords: Microsoft Kinect, VBS3, simulator, training, sensors